Perceptions of Community Resources and Insights for Program Development from Southern, Rural Hypertensive Women. (21st October 2012) - Ford, Cassandra D.; March, Alice L.
Abstract : Background . Hypertension affects millions of Americans each year and is a significant contributor to the development of cardiovascular disease. African Americans, especially those living in rural locations, experience greater disparities in the incidence and prevalence rates of hypertension and cardiovascular disease. Methods . This study utilizes qualitative descriptive methodology. Focus groups involving African American women reporting hypertension were conducted in a rural community in Alabama. Results . The mean age was 60.3 years of age (SD = 10.3). Most were married and half were college educated. The majority reported an overweight or obese status. Most were aware that they had hypertension for more than five years, all were nonsmokers, and the majority had a family history of heart disease, hypertension, and/or heart attack or stroke. Key themes emerging from the focus groups included strengths of the community, support for the community, support for a healthy lifestyle, and intervention development. Conclusion . Hypertension is a treatable and preventable disease that not only causes disability, but also significantly decreases the quality of life in affected individuals. Findings from this study provide insight into the unique needs and perceptions of African American women residing in rural Alabama as they relate to community resources.